Immature Stages of Forcipomyia-Seminole Wirth and a Related New Neotropical Species (Diptera, Ceratopogonidae) - Wirth, Willis W. (1992)
Fil: Wirth, Willis W.. Research Associate. Florida State Collection of Arthropods. Florida; USA